Fluid sources and pathways of the Costa Rica erosional convergent margin - Tryon, Michael D.; Wheat, C. Geoffrey; Hilton, David R. (Geochemistry, geophysics, geosystems : G3, 2010)
The margins community has only relatively recently begun to examine the tectonics and associated hydrologic systems of erosive convergent margins, which are substantially different as compared with accretionary margins. In this respect, the type example erosive margin is the Costa Rica system, which has been the subject of numerous recent large‐scale investigations. Here pore fluids expelled at the wedge toe and at midslope mounds and mud volcanoes have been interpreted to have a common deep source of dehydrating clays, analogous to that at accretionary margins. However, we report unusually high B/Li molar ratios in pore fluids from a recent mudflow on Mound 11, offshore Costa Rica, which, together with unusually low B/Li ratios previously reported at the wedge toe, reveal that alternative fluid sources and/or processes must be operating at the Costa Rica margin. As serpentine formation is the only subduction zone process that significantly fractionates B and Li, we propose that the difference in fluid chemical composition is the result of erosion of upper plate serpentinites, ongoing serpentinization, and serpentine mineral phase transitions in the subduction channel. These processes provide both a source of fluids and fluid pathways that lead to the unique geochemical signature observed at this erosional margin. This conclusion is compatible with, and supported by, the current view of the tectonics, geology, and hydrogeology of the Costa Rica margin and the similarity of the pore fluid to that of two other convergent margins, both with known fluid/serpentinite interactions.